MLearning : mobile learning and performance in the palm of your hand - Metcalf, David (David S.) (HRD Press, 2006)
The next time you're on the road, stuck in an airport or waiting in line, don't allow your valuable time to be wasted by circumstances you can't control. Turn on your PDA, smart phone or wireless connection and use those "stolen moments" to learn. Mobile learning--or mlearning--combines the technologies of mobile communications with any electronically delivered material. This exciting new book speaks to users at the grassroots level who want to capitalize on the latest mLearning trends to learn on the go, save time and improve productivity. How is mLearning being utilized in the corporate world? What instructional design principles work and don't work? What lays ahead for ebooks, handtop computing, wearable computers, iPods? You'll get the answers to all your questions in 10 chapters that detail how to seamlessly integrate learning into your lifestyle and work style